2023
DOI: 10.3390/ma16216903
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effect of Hydrothermal Carbonization Parameters on Fuel Properties of Sewage Sludge Hydrochar

Małgorzata Hejna,
Kacper Świechowski,
Andrzej Białowiec

Abstract: In the wake of economic and population growth, increased wastewater production poses a challenge related to sewage sludge treatment, which is problematic given its high moisture content, amount, and hazardous characteristics. This study focuses on the hydrothermal carbonization of sewage sludge to produce carbonous material–hydrochar, which may be an alternative to fossil fuels. The effect of process parameters, namely, temperature (180, 240, 300 °C) and duration time (30, 90, 180 min), on hydrochar properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 84 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…Additionally, the yield decreased significantly with increasing temperature as the degree of destruction of the SS cell structure increased, promoting the hydrolysis of proteins and carbohydrates in the SS and causing more organic matter to enter the liquid phase. 27 However, it can be observed that the yield and energy recovery (ER) rate of the pre-treated SS are significantly higher than those of the original SS. It is known that proteins are easily hydrolyzed into amino acids under hydrothermal conditions and eventually flow into the liquid phase after a series of ring-closing and rearrangement reactions, leading to a decrease in ER rate and yield.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the yield decreased significantly with increasing temperature as the degree of destruction of the SS cell structure increased, promoting the hydrolysis of proteins and carbohydrates in the SS and causing more organic matter to enter the liquid phase. 27 However, it can be observed that the yield and energy recovery (ER) rate of the pre-treated SS are significantly higher than those of the original SS. It is known that proteins are easily hydrolyzed into amino acids under hydrothermal conditions and eventually flow into the liquid phase after a series of ring-closing and rearrangement reactions, leading to a decrease in ER rate and yield.…”
Section: Resultsmentioning
confidence: 99%